Application of Dispersive Liquid-Liquid Microextraction with Graphite Furnace Atomic Absorption Spectrometry for Determination of Trace Amounts of Zinc in Water Samples - Ali Mazloomifar (International Journal of Analytical Chemistry, 2013)
A selective and simple method for separation and preconcentration of zinc ions was developed by using dispersive liquid-liquid microextraction. Parameters that have an effect on the microextraction efficiency such as volume of extraction and disperser solvent, extraction time, and adding salt were investigated. Under optimum conditions, a preconcentration factor of 250 was obtained. The limit of detection (LOD) obtained under the optimal conditions was 0.09 ng mL−1. The linearity of method was obtained in range of 0.2–50 ng mL−1 with a correlation coefficient () of 0.9974. The relative standard deviation for 10 replicate determinations at 1.0 ng mL−1 of zinc was 2.53%. The proposed method was successfully applied to the analysis of zinc in water sample.